Development of organic fertilizer from food waste by composting in UTHM Pagoh - A. Hamid, Hazren; Harun, Hasnida; Sunar, Norshuhaila; Muhammad, Mimi Suliza; Hamidon, Nuramidah; Ali, R.; Ahmad, Faridah Hanim; Lim, Pei Qi (Penerbit Uthm, 2018)
From 2000 to 2017, the global urban population has increased from 2.9 billion to 4.1 billion and by 2030, it is expected to reach 5.1billion out of 8.6 billion of global population [1]. The explosion of population and increment of urbanization with changing lifestyles create more and more wastes are being generated in many cities and townships. This ever-rising shift of the world population is already evident and will produce even more remarkable amounts of urban food waste, which in turn will add pressure to the already overloaded municipal solid waste transportation system and landfill sites [2]. According to the study conducted by SWCorp showed that Malaysians generated 38,000 tonnes of solid waste daily in 2016, of which 15,000 tonnes was food waste. It found that 20%, or 3,000 tonnes, of this food waste was avoidable [3].